An insulating coating for encapsulation and a method for preparing the same, and a sulfide solid-state battery

CN122917622APending Publication Date: 2026-10-16SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611081222.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]本发明的第一目的在于提供一种用于封装的绝缘涂层,兼具优异的流动性、界面粘附性、高绝缘性及等静压后结构完整性,无需溶剂即可快速固化成膜,可有效解决传统溶剂型胶粘剂形成的涂层不均、溶剂残留等缺陷,实现硫化物固态电池极片边缘的有效绝缘防护

Benefits of technology

1、本发明采用无溶剂的聚合体系聚合形成绝缘涂层,以含有不饱和双键的烷氧基硅烷类化合物与丙烯酸酯类单体为核心聚合单体,以固态电芯侧边为基体,在紫外光引发下进行聚合反应构建聚合网络,无溶剂快速固化的同时在固态电芯侧边形成绝缘防护层,适配硫化物固态电池的高效制造需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917622A_ABST
    Figure CN122917622A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery, especially to an insulating coating for packaging and a preparation method thereof, and a sulfide solid-state battery. The present application provides an insulating coating for packaging, and raw materials for preparing the insulating coating include photocuring active monomers and comonomers; the insulating coating is mainly obtained by polymerization of the photocuring active monomers and the comonomers under the condition of ultraviolet light initiation; the photocuring active monomers include liquid unsaturated double bond containing alkoxysilane compounds; and the comonomers include liquid acrylic ester compounds. The insulating coating for packaging has excellent fluidity, interface adhesion, high insulation and structural integrity after isostatic pressing, and can be quickly cured into a film without solvent, which can effectively solve the defects such as uneven coating and solvent residue formed by traditional solvent type adhesives, and provides key support for the industrialization of sulfide solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to an insulating coating for encapsulation, a method for preparing the same, and a sulfide solid-state battery. Background Technology

[0002] Lithium-ion batteries, as highly efficient electrochemical energy storage devices, have been widely used in consumer electronics, electric vehicles, and large-scale energy storage. Stacking technology, due to its high space utilization and low structural stress, is one of the mature technologies for liquid lithium-ion batteries. In this type of battery, the flexible polymer separator is the core component, responsible for both isolating the positive and negative electrodes to prevent short circuits and adsorbing the liquid electrolyte to construct lithium-ion conduction channels. The combination of these two components achieves reliable edge insulation and energy transfer.

[0003] With the increasing demand for high energy density and high safety, sulfide solid-state batteries have become the next-generation technology, replacing both liquid electrolytes and flexible separators with brittle particulate electrolytes. While this design overcomes the performance bottlenecks of liquid systems, it also brings new problems: the particulate electrolyte cannot form a continuous insulating layer on the side of the solid-state cell like a flexible separator, and after stacking, an isostatic pressing process is required to ensure solid-solid interface contact. The high voltage during this process can easily cause deformation and misalignment of the electrode edges, further exacerbating the risk of short circuits due to direct contact between the positive and negative electrodes.

[0004] Existing technologies typically involve coating the sides of solid-state battery cells with insulating adhesive to overcome the aforementioned defects. However, traditional solvent-based adhesives require a solvent evaporation process after coating, which can easily lead to problems such as uneven coating, solvent residue, and environmental pollution.

[0005] Therefore, developing a packaging material that can meet the requirements of isostatic pressing process, while taking into account flowability, adhesion and insulation, to achieve effective insulation protection of the edges of solid-state battery electrodes has become an urgent technical problem to be solved in this field.

[0006] In view of this, the present invention is hereby proposed. Summary of the Invention

[0007] The primary objective of this invention is to provide an insulating coating for encapsulation that combines excellent flowability, interfacial adhesion, high insulation, and structural integrity after isostatic pressing. It can be rapidly cured into a film without solvent, effectively solving the defects of uneven coating and solvent residue formed by traditional solvent-based adhesives, and achieving effective insulation protection for the edges of sulfide solid-state battery electrodes.

[0008] A second objective of the present invention is to provide a method for preparing the above-described insulating coating for encapsulation.

[0009] A third objective of this invention is to provide a sulfide solid-state battery.

[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides an insulating coating for encapsulation, wherein the raw materials for preparing the insulating coating include a photocurable active monomer and a comonomer; the insulating coating is mainly obtained by polymerization of the photocurable active monomer and the comonomer under ultraviolet light initiation conditions; The photocurable active monomer includes liquid alkoxysilane compounds containing unsaturated double bonds; The comonomer includes liquid acrylate compounds.

[0011] Furthermore, the raw materials for preparing the insulating coating, by mass parts, include: 60-83 parts of the photocurable active monomer, 16-35 parts of the comonomer, and 1-5 parts of acetophenone-based photoinitiator.

[0012] Furthermore, the raw materials for preparing the insulating coating also include sulfide solid electrolytes with a median particle size of 0.5~2μm.

[0013] Furthermore, the alkoxysilane compounds containing unsaturated double bonds include at least one of allyloxytrimethoxysilane, vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0014] Furthermore, the acrylate compound includes at least one of isobornyl acrylate, 1,6-hexanediol diacrylate, and methyl methacrylate.

[0015] Furthermore, the sulfide solid electrolyte comprises Li6PS5Cl and / or Li3PS4.

[0016] Secondly, the present invention also provides a method for preparing an insulating coating for encapsulation as described above, comprising the following steps: The raw materials for preparing the insulating coating are mixed to obtain an adhesive solution; the adhesive solution is coated on the side of a solid battery cell, and a polymerization reaction occurs under ultraviolet light initiation to obtain the insulating coating; wherein, the mixing includes one-time mixing or batch mixing.

[0017] Further, the batch mixing includes: mixing the liquid raw materials for preparing the insulating coating to obtain a mixture; adding the solid raw materials for preparing the insulating coating to the mixture, mixing evenly, to obtain the adhesive solution; The solid raw materials are added in the following ways: adding the solid raw materials to the mixture all at once; or adding the solid raw materials to the mixture in batches under ultrasonic treatment or stirring.

[0018] Furthermore, the polymerization reaction is carried out under the following conditions: irradiation with a 50-200W ultraviolet lamp for 0.5-2 minutes.

[0019] Thirdly, the present invention also provides a sulfide solid-state battery, wherein the solid-state battery containing a sulfide electrolyte is subjected to isostatic pressing to obtain the sulfide solid-state battery. The solid-state battery cell has an insulating coating on its side as described above for encapsulation.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses a solvent-free polymerization system to form an insulating coating. The core monomers are alkoxysilane compounds containing unsaturated double bonds and acrylate monomers. The side of the solid battery cell is used as the substrate. The polymerization reaction is carried out under ultraviolet light to build a polymerization network. The solvent-free rapid curing process forms an insulating protective layer on the side of the solid battery cell, which meets the high-efficiency manufacturing requirements of sulfide solid batteries.

[0021] 2. In this invention, a sulfide solid electrolyte is introduced as a functional filler into the polymerization system that forms the insulating coating. It works synergistically with the polymerization system, which not only optimizes the contact state of the solid cell interface, but also complements and enhances the polymerization network, achieving a balanced optimization of properties such as fluidity, adhesion, insulation and mechanical strength.

[0022] 3. The polymer system for forming the insulating coating of this invention belongs to the ultraviolet curing system, which has both process adaptability and product reliability. With the advantages of fast curing rate and no volatile residue, the ultraviolet curing system significantly improves the production efficiency and product consistency. Moreover, the insulating coating formed after ultraviolet curing can withstand the high-pressure conditions of isostatic pressing process of sulfide solid-state batteries, ensuring the stability of the solid-state cell interface and meeting the full process requirements of high-standard sulfide solid-state battery manufacturing.

[0023] 4. The formula of this invention is simple, the raw materials are readily available, and the process is simple and easy to operate. A single coating can meet the complex working conditions of side packaging of solid-state cells and meet the needs of large-scale production. It is suitable for promotion and application in the field of solid-state batteries. Attached Figure Description

[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.

[0025] Figure 1This is a magnified optical microscope photograph (10x magnification) of the side edge of the solid battery cell before brush coating in Embodiment 1 of the present invention. Figure 2 This is a magnified optical microscope image of the side edge of the solid-state battery cell after brush coating in Embodiment 1 of the present invention, magnified 10 times. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0027] In some embodiments of the present invention, an insulating coating for encapsulation is provided, wherein the raw materials for preparing the insulating coating include photocurable active monomers and comonomers; the insulating coating is mainly obtained by polymerization of photocurable active monomers and comonomers under ultraviolet light initiation conditions; Photocurable reactive monomers include liquid alkoxysilane compounds containing unsaturated double bonds; Comonomers include liquid acrylate compounds.

[0028] In some embodiments of the present invention, the raw materials for preparing the insulating coating do not include solvents.

[0029] In some embodiments of the present invention, the insulating coating used for encapsulation is an insulating coating used for solid-state cell encapsulation; polymerization occurs on the side of the solid-state cell, and an insulating coating is formed on the side of the solid-state cell after polymerization; preferably, the solid-state cell is a cell of a sulfide solid-state battery.

[0030] To address the technical challenges of side insulation encapsulation in sulfide solid-state battery cells, current technologies generally employ a method of coating the sides of the solid-state cell with insulating adhesive. However, traditional solvent-based adhesives require a solvent evaporation process to form a film, which can easily lead to defects such as uneven coating morphology, solvent residue, and environmental pollution. This makes them unsuitable for the stringent requirements of sulfide solid-state batteries for highly dense, residue-free, and interface-stable insulating coatings.

[0031] The polymer system for forming the insulating coating of the present invention belongs to the UV-curable adhesive system. The UV-curable adhesive system has significant advantages in terms of penetration ability, curing efficiency and environmental friendliness. Before curing, it exists in the form of small molecule liquid monomers, which can quickly penetrate into the micro-pores at the edge of the electrode in the solid-state battery cell. It does not rely on solvents and can achieve rapid curing without volatile residues, which better meets the comprehensive performance requirements of the edge insulating layer of sulfide solid-state batteries.

[0032] The polymer system for forming the insulating coating of the present invention has excellent flowability, interfacial adhesion, high insulation and structural integrity after isostatic pressing. It can be rapidly cured into a film without solvent, which can effectively solve the defects of uneven coating and solvent residue formed by traditional solvent-based adhesives, and provide key support for the industrialization of sulfide all-solid-state batteries.

[0033] This invention employs a solvent-free polymerization system to form an insulating coating in solid-state battery cell side-packaging scenarios. The core monomers are alkoxysilane compounds containing unsaturated double bonds and acrylate monomers. Using the solid-state battery cell side as the substrate, a polymerization network is constructed through a polymerization reaction initiated by ultraviolet light. This solvent-free, rapid curing simultaneously forms an insulating protective layer on the solid-state battery cell side. The fast curing rate and absence of volatile residues significantly improve the production efficiency and consistency of the insulating layer. The cured insulating coating can withstand the high-voltage conditions of isostatic pressing processes in solid-state batteries, ensuring the stability of the solid-state battery cell interface. This meets the high-efficiency manufacturing requirements of sulfide solid-state batteries.

[0034] In some embodiments of the present invention, the raw materials for preparing the insulating coating, by weight, include: 60-83 parts of photocurable active monomer, 16-35 parts of comonomer, and 1-5 parts of acetophenone-based photoinitiator.

[0035] Based on the high fluidity, sealing, and insulation requirements of solid-state battery cell edge insulation encapsulation, this invention provides an insulating coating adapted to UV curing processes, possessing excellent fluidity, interfacial adhesion, high insulation, and structural integrity after isostatic pressing. It only requires coating a polymer system of photocurable active monomers and comonomers onto the side of the solid-state battery cell, and UV curing forms the encapsulation insulating coating. This polymer system uses alkoxysilane compounds containing unsaturated double bonds as the core photocurable active monomer. On the solid-state battery cell substrate, the siloxane structure enhances the wettability and adhesion of the coating to the metal current collector surface. Combined with an acetophenone-based photoinitiator, it rapidly decomposes under UV light to generate free radicals, initiating a free radical polymerization reaction between the alkoxysilane containing unsaturated double bonds and the acrylate comonomer. By controlling the type and proportion of acrylate compounds, the hardness and modulus of the cured insulating coating can be flexibly adjusted. The synergistic effect of the components results in an insulating coating with excellent fluidity during coating and high density after curing.

[0036] In some different embodiments of the present invention, the mass fractions of the raw materials for preparing the insulating coating can be as follows: The mass fractions of the photocurable reactive monomer can be 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 83 parts, or any value between any two of these. The mass fractions of the comonomer can be 16 parts, 20 parts, 25 parts, 30 parts, 35 parts, or any value between any two of these. The mass fractions of acetophenone photoinitiators can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, or any value between any two of these.

[0037] In some embodiments of the present invention, the raw materials for preparing the insulating coating further include a sulfide solid electrolyte with a median particle size of 0.5 to 2 μm; typically, but not limitingly, the median particle size of the sulfide solid electrolyte can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, and any value between any two thereof. The median particle size is the average particle size D. 50 .

[0038] This invention introduces small-particle-size sulfide solid electrolyte as a functional filler into the polymerization system that forms the insulating coating. It works synergistically with the polymerization system, which not only optimizes the contact state of the solid cell interface, but also complements and enhances the polymerization network, achieving a balanced optimization of properties such as flowability, adhesion, insulation and mechanical strength.

[0039] When the median particle size of sulfide solid electrolyte is greater than 2.0 μm, it cannot penetrate into the micro-pores at the edge of the solid cell electrode as a large particle filler, and it is prone to become a stress concentration point during isostatic pressing, which may lead to short circuit risk.

[0040] In some embodiments of the present invention, the raw materials for preparing the insulating coating also include a thickening thixotropic agent.

[0041] The isostatic pressing process for solid-state batteries places extremely high demands on the interfacial stability of the components. If voids exist at the interface, the high pressure during isostatic pressing can cause uneven deformation of the electrode and electrolyte layers, easily leading to interfacial cracking, interlayer delamination, and even short circuits caused by conductive burrs piercing the insulating coating. Simultaneously, voids reduce ion conduction efficiency, significantly impacting the structural integrity and electrochemical performance of the battery. While UV-polymerization systems possess rapid curing characteristics, their fast curing rate often results in insufficient system leveling and interfacial wetting, making it difficult to form a highly dense interfacial bonding layer. This poses a key technical challenge for adapting this system to the preparation of insulating coatings for solid-state batteries. This invention further incorporates small-particle-size sulfide electrolyte powder and / or thickening thixotropic agents as functional fillers into the UV-polymerization system. The micron-sized solid raw materials fill the interfacial voids at the edges of the electrode inside the cell, synergistically enhancing the insulation reliability and interfacial stability of the coating through the UV-polymerization system. This provides structural support and performance assurance for an insulating coating with strong adhesion, high insulation, and isostatic pressing resistance. Among them, sulfide electrolytes have lithium-ion conductivity, which is more conducive to improving the performance of solid-state batteries.

[0042] In some embodiments of the present invention, the mass of the photocurable active monomer accounts for 60% to 83% of the total mass of the raw materials used to prepare the insulating coating.

[0043] In some embodiments of the present invention, the mass of the comonomer accounts for 16% to 35% of the total mass of the raw materials used to prepare the insulating coating.

[0044] In some embodiments of the present invention, the mass ratio of the photocurable active monomer to the comonomer is (2~4.5):1; typically, but not limitingly, for example, the mass ratio of the photocurable active monomer to the comonomer can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, and any value between any two thereof. A mass ratio that is too large or too small for the photocurable active monomer and the comonomer will result in a significant decrease in the adhesion of the coating to the metal current collector, leading to interlayer delamination after isostatic pressing.

[0045] In some embodiments of the present invention, the mass of the acetophenone-based photoinitiator accounts for 1% to 5% of the total mass of the raw materials used to prepare the insulating coating.

[0046] In some embodiments of the present invention, the mass of the sulfide solid electrolyte accounts for 1% to 8% of the total mass of the raw materials for preparing the insulating coating; typically, but not limitingly, for example, the mass of the sulfide solid electrolyte accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% of the total mass of the raw materials for preparing the insulating coating, and any value between any two thereof; preferably, the mass of the sulfide solid electrolyte accounts for 2% to 6% of the total mass of the raw materials for preparing the insulating coating.

[0047] In some embodiments of the present invention, the mass of the thickening thixotropic agent accounts for 1% to 5% of the total mass of the raw materials for preparing the insulating coating; typically, but not limitingly, for example, the mass of the thickening thixotropic agent accounts for 1%, 2%, 3%, 4%, 5% of the total mass of the raw materials for preparing the insulating coating, and any value between any two thereof; preferably, the mass of the thickening thixotropic agent accounts for 2% to 4% of the total mass of the raw materials for preparing the insulating coating.

[0048] To address the technical challenge of side insulation encapsulation in sulfide-based solid-state battery cells, this invention provides an insulating coating for encapsulation. This coating uses alkoxysilane compounds containing unsaturated double bonds as photocurable polymer monomers, supplemented with acrylate comonomers, and combined with sulfide solid electrolytes or thickening thixotropic agents as functional fillers. Through the scientific ratio and synergistic effect of specific components, an insulating coating with excellent flowability, strong adhesion, high insulation, and good isostatic pressure resistance is directly formed on the side of the solid-state battery cell under ultraviolet light initiation conditions. This effectively solves the problem of insulation protection at the edges of sulfide-based solid-state battery electrodes.

[0049] In some preferred embodiments of the present invention, the alkoxysilane compounds containing unsaturated double bonds include at least one of allyloxytrimethoxysilane, vinyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and 3-acryloyloxypropyltrimethoxysilane.

[0050] Compared to other types of alkoxysilane compounds, such as vinyltriethoxysilane, the alkoxysilane compounds of the present invention exhibit better wettability and reactivity in the polymerization system of the present invention, which are more suitable for the side environment of solid-state battery cells. The polymerization system of the present invention requires both strong initial flowability and weak flowability after curing; under the same curing conditions, vinyltriethoxysilane has strong flowability (stronger than vinyltrimethoxysilane), and under isostatic pressing, it is easy to expose the metal foil under pressure, causing a short circuit.

[0051] In some preferred embodiments of the present invention, the acrylate compound includes at least one of isobornyl acrylate, 1,6-hexanediol diacrylate and methyl methacrylate.

[0052] The use of the acrylate compounds of the above-mentioned types in this invention ensures the mechanical properties of the insulating coating; while other types of acrylate compounds, such as lauryl acrylate (long-chain alkyl), will significantly reduce the crosslinking density and hardness of the insulating coating, causing the coating to be prone to plastic casting or structural damage under isostatic pressure (100~200MPa) high pressure conditions.

[0053] In some embodiments of the present invention, the acetophenone photoinitiator includes at least one of 2-hydroxy-2-methylacetophenone, 1-hydroxycyclohexyl acetophenone, and 2,2-diethoxyacetophenone.

[0054] Compared to phosphine oxide initiators, which have a lower compatibility with the alkoxysilane and acrylate system of the present invention, resulting in incomplete deep curing and affecting the consistency of the coating, the acetophenone photoinitiators of the present invention have a high compatibility with the polymerization system of alkoxysilane and acrylate of the present invention, ensuring complete curing of the coating.

[0055] In some embodiments of the present invention, the sulfide solid electrolyte includes Li6PS5Cl and / or Li3PS4.

[0056] In some embodiments of the present invention, the thickening thixotropic agent includes at least one of fumed silica, nano-titanium dioxide, nano-boron nitride, and organobentonite; preferably, the thickening thixotropic agent includes fumed silica.

[0057] The lack of sulfide solid electrolyte or thickening thixotropic agent will affect the performance of the insulating coating. If no thickening thixotropic agent is added, the lack of thixotropy will cause the polymer system to easily sag or have uneven thickness when coated on the side of the solid cell, and it will be impossible to form a complete insulating coating under complex working conditions.

[0058] In some embodiments of the present invention, a method for preparing an insulating coating for encapsulation is also provided, comprising the following steps: The raw materials for preparing the insulating coating are mixed to obtain a glue solution; the glue solution is coated on the side of a solid battery cell, and a polymerization reaction occurs under ultraviolet light initiation to obtain the insulating coating. Mixing can include one-time mixing or batch mixing.

[0059] In some embodiments of the present invention, batch mixing includes: mixing liquid raw materials for preparing an insulating coating to obtain a mixture; adding solid raw materials for preparing an insulating coating to the mixture, mixing evenly to obtain an adhesive solution.

[0060] In some embodiments of the present invention, the addition method includes: adding solid raw materials to the mixture all at once; or adding solid raw materials to the mixture in batches under ultrasonic treatment or stirring; preferably, the ultrasonic treatment power is 250~350W, and the stirring speed is 1000~2000rpm.

[0061] In some embodiments of the present invention, the raw materials for preparing the insulating coating include liquid raw materials such as photocurable active monomers, comonomers and acetophenone-based photoinitiators; and solid raw materials such as sulfide solid electrolytes and / or thickening thixotropic agents.

[0062] It should be noted that the liquid and solid raw materials involved in this invention refer to the phase state at room temperature.

[0063] This invention adapts to different filler characteristics and formulation systems through a flexible solid-liquid mixing method, ensuring uniform dispersion of solid raw materials in liquid polymer raw material systems, giving the adhesive suitable fluidity and improving coating uniformity, thereby improving the overall performance consistency of the insulating protective layer.

[0064] In some embodiments of the present invention, the polymerization reaction conditions are: irradiation with a 50-200W ultraviolet lamp for 0.5-2 minutes; preferably, the polymerization reaction conditions are: irradiation with a 100W ultraviolet lamp for 1 minute.

[0065] In some embodiments of the present invention, a sulfide solid-state battery is also provided, wherein a solid cell containing a sulfide electrolyte is subjected to isostatic pressing to obtain a sulfide solid-state battery. The solid-state battery cell has the aforementioned insulating coating used for encapsulation on its side.

[0066] The insulating coating for encapsulation of the present invention can withstand the high-pressure conditions of isostatic pressing processes for sulfide solid-state batteries, ensuring the stability of the solid-state cell interface. A single coating can adapt to the complex operating conditions of side encapsulation of solid-state cells, meeting the full-process requirements of high-standard sulfide solid-state battery manufacturing.

[0067] In some embodiments of the present invention, the conditions for isostatic pressing are: temperature 60~90℃, pressure 100~200MPa, and time 10~30min.

[0068] It should be noted that the solid cell side (also commonly referred to as the solid cell electrode side or solid cell edge) involved in this invention refers to the circumferential area on the side formed by the stacking / winding of the electrode (positive electrode and negative electrode) and the solid electrolyte layer of sulfide all-solid battery cells. It corresponds to the non-active end face of the cell core and is a key weak part of the cell structure.

[0069] Information on some of the raw materials used in the embodiments and comparative examples of this invention is as follows: Fumed silica, sourced from Shandong Dongyue Organosilicon Materials Co., Ltd., model number B-100; Bisphenol A type epoxy resin: sourced from Yueyang Baling Huaxing Petrochemical Co., Ltd., model number CYD-128Y; Boron nitride powder: sourced from Shandong Fangyuan High Conductivity Special Ceramics Materials Co., Ltd., model number HBN-A1.

[0070] Unless otherwise specified, all raw materials, equipment and other consumables involved in this invention are commercially available.

[0071] Example 1 The method for preparing the insulating coating for encapsulation provided in this embodiment includes the following steps: S1, 15.6g of allyloxytrimethylsilane, 3.6g of methyl methacrylate, 0.4g of 2,2-diethoxyacetophenone, and Li6PS5Cl (particle size D) 50 0.4g of the sample (1μm) was placed in a container and stirred at 500rpm for 30min at room temperature (25℃) using a mechanical stirrer to obtain a uniformly dispersed transparent liquid. S2. Apply the above adhesive to the side edge of the solid battery cell and place it under a 100W ultraviolet lamp for 1 minute to carry out the polymerization reaction. After the polymerization reaction is completed, an insulating coating with a thickness of 0.01~0.02mm is formed on the side edge of the solid battery cell.

[0072] An optical microscope image of the side edge of the solid-state battery cell before brush coating in Example 1 is shown below. Figure 1 As shown; an optical microscope image of the side edge of the solid-state battery cell after brushing (with an insulating coating formed at the edge). Figure 2 As shown.

[0073] Example 2 The method for preparing the insulating coating for encapsulation provided in this embodiment refers to Embodiment 1, except that in step S1, 14.0 g of vinyltrimethoxysilane, 5.0 g of isobornyl acrylate, and 0.6 g of 2-hydroxy-2-methylphenylacetone are placed in a container and stirred at 200 rpm for 10 min using a planetary mixer. Then, Li6PS5Cl (particle size D) is added. 50 0.4 g of 1 μm solution was stirred at 800 rpm for 40 min, and the system temperature was kept below 35 °C by circulating water cooling during the stirring process; a uniformly dispersed gel solution was obtained.

[0074] Example 3 The method for preparing the insulating coating for encapsulation provided in this embodiment is the same as in Example 1, except that in step S1, 12.0 g of γ-methacryloyloxypropyltrimethoxysilane, 6.0 g of 1,6-hexanediol diacrylate, and 0.8 g of 1-hydroxycyclohexylbenzophenone are placed in a light-proof container and stirred at 200 rpm for 15 min using a magnetic stirrer. Then, the mixture is transferred to an ultrasonic cell disruptor (300 W) for ultrasonic treatment, and Li3PS4 (particle size D) is slowly added in two batches. 50 1.2g of 0.8μm gel was ultrasonically treated for a total of 20min to obtain a uniformly dispersed gel.

[0075] Example 4 The method for preparing the insulating coating for encapsulation provided in this embodiment refers to Example 1, except that in step S1, 15.0g of 3-acryloyloxypropyltrimethoxysilane, 4.0g of methyl methacrylate and 0.4g of 2,2-diethoxyacetophenone are mixed evenly, and 0.6g of thickening thixotropic agent (fumed silica) is added under the continuous stirring action of a high-speed disperser (speed of 1500 rpm). The mixture is continuously dispersed for 60min until the system presents a uniform thixotropic paste with no visible particles or agglomerates, thus obtaining a uniformly dispersed adhesive.

[0076] Comparative Example 1 The preparation method of the insulating coating provided in this comparative example is the same as that in Example 1, except that in step S1, 5.0 g of bisphenol A type epoxy resin, 1.6 g of methyl hexahydrophthalic anhydride, 12.4 g of N,N-dimethylformamide and 1.0 g of boron nitride powder are added to a ball mill jar and mixed with zirconia balls at a speed of 150 rpm for 24 h to obtain a uniformly dispersed adhesive solution.

[0077] Comparative Example 2 The preparation method of the insulating coating provided in this comparative example is the same as that in Example 1, except that in step S1, 16.4 g of trimethylolpropane triacrylate, 3.0 g of n-butyl acrylate and 0.6 g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are placed in a light-proof container and stirred and mixed at 400 rpm for 25 min at room temperature (25°C) in the dark to obtain a uniformly dispersed adhesive solution.

[0078] Comparative Example 3 The method for preparing the insulating coating provided in this comparative example is the same as in Example 1, except that in step S1, allyloxytrimethylsilane is replaced with vinyltriethoxysilane.

[0079] Comparative Example 4 The method for preparing the insulating coating provided in this comparative example is the same as in Example 1, except that in step S1, methyl methacrylate is replaced with lauryl acrylate.

[0080] Comparative Example 5 The method for preparing the insulating coating provided in this comparative example is the same as in Example 1, except that in step S1, 2,2-diethoxyacetophenone is replaced with phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0081] Comparative Example 6 The method for preparing the insulating coating provided in this comparative example is the same as in Example 1, except that in step S1, the particle size D of Li6PS5Cl is... 50 It is 5μm.

[0082] Comparative Example 7 The preparation method of the insulating coating provided in this comparative example refers to Example 1, with the only difference being that in step S1, the mass of allyloxytrimethylsilane is 9.6 g, and the mass of methyl methacrylate is 9.6 g.

[0083] Comparative Example 8 The preparation method of the insulating coating provided in this comparative example refers to Example 4, with the only difference being that no thickening thixotropic agent (fumed silica) is added in step S1.

[0084] Test Example The solid-state cells with insulating coatings formed on their side edges in Examples 1 to 4 and Comparative Examples 1 to 8 are respectively placed in an isostatic press for isostatic treatment at a temperature of 80°C, a pressure of 120 MPa, and a duration of 20 min, to obtain sulfide solid-state batteries; Wherein, the solid-state cell is an alternating stack of positive electrode sheet-sulfide electrolyte layer-negative electrode sheet; The preparation method of the positive electrode sheet is: mixing NCM811, Li6PS5Cl electrolyte, carbon black and polyisobutylene at a mass ratio of 70:20:5:5 in toluene to form a slurry, which is coated on an aluminum foil to serve as the positive electrode; The preparation method of the negative electrode sheet is: mixing silicon-carbon material, Li6PS5Cl electrolyte, carbon black and polyisobutylene at a mass ratio of 75:15:5:5 in toluene to form a slurry, which is coated on an aluminum foil to serve as the negative electrode.

[0085] The material of the sulfide electrolyte layer is LPSC.

[0086] The sulfide solid-state batteries after isostatic treatment are used as test samples, and the open circuit voltage (OCV) between the positive and negative current collectors of the battery cell is tested; a voltage greater than 0.2 V is recorded as qualified; a voltage ≤ 0.2 V indicates that there is a micro-short circuit or insulation failure between the positive and negative current collectors of the cell, so a voltage ≤ 0.2 V is unqualified. 50 parallel battery samples are set for each Example and Comparative Example for testing, the number of qualified samples is recorded and the qualification rate is calculated as shown in Table 1.

[0087] Table 1

[0088] As shown in Table 1, the polymerization system of the present invention for forming the insulating coating can produce an insulating coating with excellent flowability, strong adhesion, high insulation, and reliable isostatic pressure resistance, providing effective insulation protection for the edges of the sulfide all-solid-state battery electrodes, and ultimately achieving a solid-state battery yield of over 80%. In contrast, Comparative Example 1 used a traditional solvent-based curing system, and the polymerization systems of Comparative Examples 2-8 did not use the raw materials of the present invention. The resulting insulating coatings had poorer performance, and the yield of the prepared solid-state batteries was significantly lower, failing to meet the high requirements of solid-state batteries under isostatic pressure conditions.

[0089] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. An insulating coating for encapsulation, characterized in that, The raw materials for preparing the insulating coating include photocurable active monomers and comonomers; the insulating coating is mainly obtained by polymerization of the photocurable active monomers and the comonomers under ultraviolet light initiation conditions; The photocurable active monomer includes liquid alkoxysilane compounds containing unsaturated double bonds; The comonomer includes liquid acrylate compounds.

2. The insulating coating for encapsulation according to claim 1, characterized in that, The raw materials for preparing the insulating coating, by mass parts, include: 60-83 parts of the photocurable active monomer, 16-35 parts of the comonomer, and 1-5 parts of acetophenone-based photoinitiator.

3. The insulating coating for encapsulation according to claim 2, characterized in that, The raw materials for preparing the insulating coating also include sulfide solid electrolytes with a median particle size of 0.5~2μm.

4. The insulating coating for encapsulation according to claim 2, characterized in that, The alkoxysilane compounds containing unsaturated double bonds include at least one of allyloxytrimethoxysilane, vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and 3-acryloxypropyltrimethoxysilane.

5. The insulating coating for encapsulation according to claim 2, characterized in that, The acrylate compounds include at least one of isobornyl acrylate, 1,6-hexanediol diacrylate, and methyl methacrylate.

6. The insulating coating for encapsulation according to claim 3, characterized in that, The sulfide solid electrolyte includes Li6PS5Cl and / or Li3PS4.

7. The method for preparing the insulating coating for encapsulation according to any one of claims 1 to 6, characterized in that, Includes the following steps: The raw materials for preparing the insulating coating are mixed to obtain an adhesive solution; the adhesive solution is coated on the side of a solid battery cell, and a polymerization reaction occurs under ultraviolet light initiation to obtain the insulating coating; wherein, the mixing includes one-time mixing or batch mixing.

8. The method for preparing the insulating coating for encapsulation according to claim 7, characterized in that, The batch mixing includes: mixing the liquid raw materials for preparing the insulating coating to obtain a mixture; adding the solid raw materials for preparing the insulating coating to the mixture, mixing evenly to obtain the adhesive solution; The solid raw materials are added in the following ways: adding the solid raw materials to the mixture all at once; or adding the solid raw materials to the mixture in batches under ultrasonic treatment or stirring.

9. The method for preparing the insulating coating for encapsulation according to claim 7, characterized in that, The polymerization reaction conditions are: irradiation with a 50-200W ultraviolet lamp for 0.5-2 minutes.

10. A sulfide solid-state battery, characterized in that, The sulfide solid battery is obtained by isostatic pressing a solid cell containing a sulfide electrolyte. The solid-state battery cell has an insulating coating for encapsulation as described in any one of claims 1 to 6 on its side.